Using Group Investigation (GI) Strategy to Improve Students’ Writing Skill - Ayu, Renada Puji; Supiah, Supiah; Rasuan, Zulfikri B; Rahmaniyar, Atik (EEdJ: English Education Journal, 2022)
The aim of this research is to find out the effectiveness of Group Investigation Strategy in improving students’ writing skill This study is experimental and was conducted in Bangka, Bangka Belitung province. 50 students from two classes of middle school were taken as the sample. By using Paired Sample t-test and Independent Sample t-test, the result showed that the students who were taught by using Group Investigation Strategy got higher score than those who were not. The result of independent sample t-test stated that t-obtained (0.420) was lower than critical value of t- table (2.01) and the significant (2-tailed) was 0.670, higher than computation with significant level 0.005. In other words, there was a no significant difference between students who were taught by using Group Investigation Strategy and the students who were taught without using Group Investigation Strategy.